On the Identity of Trichocentrum orthoplectron (Orchidaceae: Oncidiinae), with a new species from Bolivia - Pupulin, Franco (2018)
The species traditionally included under the synonymy of Trichocentrum albococcineum are re-evaluated, and T. orthoplectron is reinstated as a separate species. A new species of Trichocentrum from Bolivia, T. moreniorum, is described and illustrated, and its relationships with other species of the genus are discussed. A key to the species of the Trichocentrum fuscum group is presented.